2017
DOI: 10.1051/matecconf/201710302001
|View full text |Cite
|
Sign up to set email alerts
|

The Recent Research on Bamboo Reinforced Concrete

Abstract: Abstract. The paper presents the last research on bamboo reinforced concrete in Brawijaya University Indonesia. Three kinds of structures studied in recent year, the mounting of pegs on reinforcement, the use of lightweight brick to reduce the weight of the beams, and the use the light weight aggregate for bamboo concrete composite frame. All that experiments overcome some problems exist in using bamboo as environmental acceptance structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…This is one of the problem solutions of the low capacity of bamboo reinforced concrete beams. Earlier researchers concluded that the bending capacity of bamboo reinforced concrete beams only reached 56% of its capacity if full bamboo tensile strength [15], reaching only 29% to 39% of the steel reinforced concrete beam capacity with the same dimensions and breadth area [16], and just reached 35% of steel reinforced concrete beams at the same level of strength [17,18]. 35.0 6.9 6.9 6.9 6.9 6.51 6.39 Fig.…”
Section: Pull Out Tests Resultsmentioning
confidence: 99%
“…This is one of the problem solutions of the low capacity of bamboo reinforced concrete beams. Earlier researchers concluded that the bending capacity of bamboo reinforced concrete beams only reached 56% of its capacity if full bamboo tensile strength [15], reaching only 29% to 39% of the steel reinforced concrete beam capacity with the same dimensions and breadth area [16], and just reached 35% of steel reinforced concrete beams at the same level of strength [17,18]. 35.0 6.9 6.9 6.9 6.9 6.51 6.39 Fig.…”
Section: Pull Out Tests Resultsmentioning
confidence: 99%
“…As is known, the researchers concluded that the ultimate load of BRC beams is very low when compared to the theoretical calculations. Dewi et al (2017) [42] concluded that the bending capacity of bamboo reinforced concrete beams only reaches 56% of its capacity if the tensile strength of bamboo is full. Nathan (2014) [43] concluded that the flexural capacity of reinforced concrete beams only reaches 29% to 39% of the beam capacity steel-reinforced concrete with the same width and reinforcement dimensions.…”
Section: Methodsmentioning
confidence: 99%
“…Penggunaan bambu sebagai bahan bangunan konstruksi telah banyak digunakan oleh masyarakat pedesaan, seperti konstruksi rumah tinggal sederhana, rangka jembatan semi permanen, konstruksi rangka gudang, konstruksi turap pada saluran irigasi, dan sebagainya. Bahkan penggunaan bambu sebagai material alternatif pengganti tulangan baja dalam konstruksi beton telah banyak dilakukan oleh peneliti, diantaranya Ghavami (2005), Dewi & Nuralinah (2017), Mali & Datta (2020), Kathiravan et al (2020), Muhtar et al (2019), dan lain-lain. Alasan bambu digunakan sebagai material alternatif tulangan baja karena kuat tariknya yang cukup tinggi.…”
Section: Pendahuluanunclassified